Association of rs61803665 Polymorphism in the F11R Gene with Increased Risk of Gastric Cancer - Khalili, Zahra; Moghanibashi, Mehdi; Ghaderi, Abbas (Asian Pacific Journal of Cancer Biology, 2019)
Introduction and Objectives: Gastric cancer is one of the most common cancers throughout the world and it is classified as a multifactorial disease. F11R is one of the genes whose role in different cancers is proven. As miR-335-5p and miR-638 are involved in the control of F11R gene expression, and rs61803665 in the F11R gene is located at the binding site to this miRs, we investigated the possible association of this polymorphism with the risk of gastric cancer. Materials and Methods: 189 gastric cancer patients and 190 healthy individuals were enrolled in this case-control study. Genomic DNA was extracted from blood samples of the patient and the control groups. Using PCR-RLFP technique, the genotype of all samples for rs61803665 in the F11R gene was determined. The results were analyzed statistically using logistic regression and Chi-square tests. Results: The frequency of genotype AA, AG and GG in the control group were 27.90%, 40.52%, and 31.58%, respectively. The frequency of genotype AA, AG and GG in the patient groups were 24.34%, 30.68%, and 44.98%, respectively. The frequency of allele A and allele G in the control group were 48.15% and 51.85%, respectively. Besides, the frequency of allele A and allele G in the patient groups were 39.68% and 60.32%, respectively. Based on the results of statistical tests, there is a significant correlation between the risk of gastric cancer and genotype GG (P = 0.008, OR = 1.771, % 95CI=1.164-2.693) and allele G (P = 0/019, OR = 1/412, 95% CI = 1/059-1/883). Conclusion: This study showed that there is an association between allele G at the rs61803665 in the F11R gene and the increased risk of gastric cancer.